Bhīmaparākramam - Ṭhākura, Rāmajī (Vidyānidhi Prakāśana, 2022)
Poems on Bhīma and Bhiṣma, Hindu mythological characters from Mahabhārata.
Poems
Keywords: Bhīma; (Hindu mythological character); Poetry.; Bhīṣma; (Hindu mythological character); Poetry.; Sanskrit poetry.